Affect, Belief, and the Arts - Gabriel, Rami (Frontiers in Psychology, 2021)
The cultural project is a therapeutic melding of emotion, symbols, and knowledge. In this paper, I describe how spiritual emotions engendered through encounters in imaginative culture enable fixation of metaphysical beliefs. Evolved affective systems are domesticated through the social practices of imaginative culture so as to adapt people to live in culturally defined cooperative groups. Secondary-level mental processes like conditioning, as well as tertiary-level cognitive capacities such as symbols and language are enlisted to bond groups through the imaginative formats of myth and participatory ritual. These cultural materializations can be shared by communities both synchronically and diachronically in works of art. In the sacred state produced through the arts and in religious acts, the sense of meaning becomes noetically distinct because affect infuses the experience of immanence, and one’s memory of it, with salience. The quality imbued thereby makes humans attentive to subtle signs and broad ‘truths.’ Saturated by the emotional experience and the consequences of alterity in the immanent encounter of imaginative culture, information made salient in the sacred experience can become the basis for belief fixation. Art is thus a form of self-knowledge that equips us with a motivated understanding of ourselves in the world. Through examples drawn from mimetic arts and arts of immanence, I put forward a theory about how sensible affective knowledge is mediated through affective systems, direct perception, and the imagination.